Out of sight, but not out of mind: Key issues regarding seafloor macrolitter monitoring - Georg Hanke; Miquel Canals; Ryota Nakajima; Melanie Bergmann; Francois Galgani; Daoji Li; George Papatheodorou; Christopher Kim Pham; Diva J. Amon; Michela Angiolillo; Lene Buhl-Mortensen; Alessandro Cau; et al. (Marine Pollution Bulletin, 2025)

Citizen science through a recreational underwater diving project supports the collection of large-scale marine litter data: The Oceania case study - V. Sciutteri; V. Costa; D. Malara; F. Figurella; I. Campbell; E. Deery; T. Romeo; F. Andaloro; P. Consoli (Marine Pollution Bulletin, 2024)

Canarian common ravens electrocution: a post-mortem case study - A. Fernandez; P. Diaz-Santana; M. Andrada; L. Marrero; P. Alonso; F. Consoli; J. Navarro; C. Fiorito; C. Díaz-Santana (Journal of Comparative Pathology, 2023)

Acute manganese exposure impairs glutamatergic function in a young mouse model of Alzheimer’s disease - Brittany D. Spitznagel; Rebecca A. Buchanan; David C. Consoli; Megan K. Thibert; Aaron B. Bowman; William P. Nobis; Fiona E. Harrison (NeuroToxicology, 2023)

Influence of offshore oil and gas structures on seascape ecological connectivity - Dianne L. McLean; Luciana C. Ferreira; Jessica A. Benthuysen; Karen J. Miller; Marie‐Lise Schläppy; Matthew J. Ajemian; Oliver Berry; Silvana N. R. Birchenough; Todd Bond; Fabio Boschetti; Ann S. Bull; Jeremy T. Claisse; et al. (Global Change Biology, 2022)
Offshore platforms, subsea pipelines, wells and related fixed structures supporting the oil and gas (O&G) industry are prevalent in oceans across the globe, with many approaching the end of their operational life and requiring decommissioning. Although structures can possess high ecological diversity and productivity, information on how they interact with broader ecological processes remains unclear. Here, we review the current state of knowledge on the role of O&G infrastructure in maintaining, altering or enhancing ecological connectivity with natural marine habitats. There is a paucity of studies on the subject with only 33 papers specifically targeting connectivity and O&G structures, although other studies provide important related information. Evidence for O&G structures facilitating vertical and horizontal seascape connectivity exists for larvae and mobile adult invertebrates, fish and megafauna; including threatened and commercially important species. The degree to which these structures represent a beneficial or detrimental net impact remains unclear, is complex and ultimately needs more research to determine the extent to which natural connectivity networks are conserved, enhanced or disrupted. We discuss the potential impacts of different decommissioning approaches on seascape connectivity and identify, through expert elicitation, critical knowledge gaps that, if addressed, may further inform decision making for the life cycle of O&G infrastructure, with relevance for other industries (e.g. renewables). The most highly ranked critical knowledge gap was a need to understand how O&G structures modify and influence the movement patterns of mobile species and dispersal stages of sessile marine species. Understanding how different decommissioning options affect species survival and movement was also highly ranked, as was understanding the extent to which O&G structures contribute to extending species distributions by providing rest stops, foraging habitat, and stepping stones. These questions could be addressed with further dedicated studies of animal movement in relation to structures using telemetry, molecular techniques and movement models. Our review and these priority questions provide a roadmap for advancing research needed to support evidence‐based decision making for decommissioning O&G infrastructure.

Fish community in a surf zone of the northern Sicilian coast (Mediterranean Sea): diversity and functional guild composition - V. ESPOSITO; L. CASTRIOTA; P. BATTAGLIA; P. CONSOLI; T. ROMEO; G. SCOTTI; F. ANDALORO (Mediterranean Marine Science, 2015)
Fish assemblage in a surf zone of the southern Tyrrhenian Sea was investigated for the first time. Samples were collected during four surveys by a modified beach-seine, from June 2005 to May 2006. Overall, 42 species belonging to 19 families were recorded. Among them, Sardina pilchardus showed the highest abundance values, while Mugilids (Oedalechilus labeo and Liza aurata) were the most frequently caught species. The fish community was dominated by pelagic and gregarious species using this habitat as a foraging ground and recruitment area. Juveniles and early adults made up the largest proportion of the ichthyofauna. Fishes inhabiting the surf zone were mainly strictly benthic invertebrate feeders and invertivorous/piscivorous fish; strictly planktivorous were represented by few species but strongly dominant in terms of catch per unit effort; strictly piscivorous fish were poorly represented. Fish composition varied over the study period with the greatest abundance in May and December, and the highest richness and diversity in October.

New Mediterranean Biodiversity Records (October, 2014) - S. KATSANEVAKIS; Ü. ACAR; I. AMMAR; B. A. BALCI; P. BEKAS; M. BELMONTE; C. C. CHINTIROGLOU; P. CONSOLI; M. DIMIZA; K. FRYGANIOTIS; V. GEROVASILEIOU; V. GNISCI; et al. (Mediterranean Marine Science, 2014)
The Collective Article ‘New Mediterranean Biodiversity Records’ of the Mediterranean Marine Science journal offers the means to publish biodiversity records in the Mediterranean Sea. The current article is divided in two parts, for records of alien and native species respectively. The new records of alien species include: the red alga Asparagopsis taxiformis (Crete and Lakonicos Gulf) (Greece); the red alga Grateloupia turuturu (along the Israeli Mediterranean shore); the mantis shrimp Clorida albolitura (Gulf of Antalya, Turkey); the mud crab Dyspanopeus sayi (Mar Piccolo of Taranto, Ionian Sea); the blue crab Callinectes sapidus (Chios Island, Greece); the isopod Paracerceis sculpta (northern Aegean Sea, Greece); the sea urchin Diadema setosum (Gökova Bay, Turkey); the molluscs Smaragdia souverbiana, Murex forskoehlii, Fusinus verrucosus, Circenita callipyga, and Aplysia dactylomela (Syria); the cephalaspidean mollusc Haminoea cyanomarginata (Baia di Puolo, Massa Lubrense, Campania, southern Italy); the topmouth gudgeon Pseudorasbora parva (Civitavecchia, Tyrrhenian Sea); the fangtooth moray Enchelycore anatine (Plemmirio marine reserve, Sicily); the silver-cheeked toadfish Lagocephalus sceleratus (Saros Bay, Turkey; and Ibiza channel, Spain); the Indo-Pacific ascidian Herdmania momusin Kastelorizo Island (Greece); and the foraminiferal Clavulina multicam erata (Saronikos Gulf, Greece). The record of L. sceleratus in Spain consists the deepest (350-400m depth) record of the species in the Mediterranean Sea. The new records of native species include: first record of the ctenophore Cestum veneris in Turkish marine waters; the presence of Holothuria tubulosa and Holothuria polii in the Bay of Igoumenitsa (Greece); the first recorded sighting of the bull ray Pteromylaeus bovinus in Maltese waters; and a new record of the fish Lobotes surinamensis from Maliakos Gulf.

Bathymetric and longitudinal distribution analyysis of the rockfish Helicolenus Dactylopterus (Delaroche, 1809) in the southern Tyrrhenian Sea (central Mediterranean) - T. ROMEO; L. CASTRIOTA; P. CONSOLI; M. FALAUTANO; G. FLORIO; F. PERDICHIZZI; M.G. FINOIA; F. ANDALORO; P. RINELLI (Mediterranean Marine Science, 2009)
This study provides information on bathymetric and longitudinal distribution heterogeneity of the rockfish Helicolenus dactylopterus in the southern Tyrrhenian Sea. Data were drawn from experimental bottom trawl (1996-2002) plus bottom trap (2001-02) surveys. The frequency of occurrence and mean relative density (N/km2) and biomass (kg/km2) indexes were calculated for two survey seasons (spring and autumn), four geographic sectors and three depth strata. MANOVA was used to test fish abundance among years, sectors and strata. Analysis of the length-frequency distributions was carried out by two-way (gears and depths) ANOVA, post hoc multiple comparisons for testing differences among depths and Student’s t test for testing differences between gears. Length-weight relationship was also estimated and the allometric coefficient was tested with the Student’s t test. The results showed a significant positive bathymetric gradient of sizes both for trawl and trap surveys; at same depths, fish caught by traps were significantly longer than those caught by trawl. In spring surveys, significant differences were found among strata for both abundance indexes; in autumn surveys, significant differences between depth strata were found only for density indices. The distribution and abundance patterns of H. dactylopterus along the southern Tyrrhenian Sea was homogeneous among sectors. Length-weight relationship showed a significant positive allometric growth.

Feeding habits of the albacore tuna Thunnus alalunga (Perciformes, Scombridae) from central Mediterranean Sea - P. Consoli; T. Romeo; P. Battaglia; L. Castriota; V. Esposito; F. Andaloro (Marine Biology, 2008)

Cellular and molecular effects of protons: Apoptosis induction and potential implications for cancer therapy - C. Di Pietro; S. Piro; G. Tabbì; M. Ragusa; V. Di Pietro; V. Zimmitti; F. Cuda; M. Anello; U. Consoli; E. T. Salinaro; M. Caruso; C. Vancheri; et al. (Apoptosis, 2006)

Morphometric aspects of Scyllarides latus - T. ROMEO; G. FLORIO; F. LENTINI; L. CASTRIOTA; M. FALAUTANO; P. CONSOLI; P. PELUSI; S. GRECO (Mediterranean Marine Science, 2004)
The slipper lobster, Scyllarides latus (Latreille, 1803), is the only representative species of the genusScyllarides in the Mediterranean Sea. In this study, we examined some biological aspects of this species sampled in the Straits of Messina. The specimens were sexed, measured and weighed. The relationships between body measurements (length and width of the carapace, antennal length) and length-weight relationship were calculated. Furthermore, the correlation matrix (Pearson’s coefficient) was calculated. Two hundred specimens were collected, ranging in size from 81 to 305 mm in total length, and between 21 and 1490 g in weight. A rare juvenile of 39 mm CL was recorded. A sex ratio of 1:1 was found. The carapace length – weight relationship was almost isometric. The wide size range sampled and the presence of a juvenile, indicate an interesting habitat for studying the presence and growth of Scyllarides latus in the Straits of Messina.